SUPPORT PENDDIDIKAN PERAWAT DENGAN TEKNOLOGI CLICKERS PUJI ASTUTI - Puji Astuti (Jurnal Ilmiah Kesehatan, 2013)
The educational process in nursing recently shows a rapid development, a variety of learning methods are applied to achieve the learning objectives, and even the use of computer has become a student need. Nursing education now is widely supported by technologies, one of them is Clickers. Clickers is Student Response Systems. The purpose of this article is studying and discussing the literature about Clickers technology and its application analysis in support of education The result is a lot of research trying to apply the clickers in the classlearning and produce results that Clickers help in understanding the content and bring greater student involvement during lectures, student feel satisfied and the learning outcomes are increased. Clickers is supporting the teaching and learning activities in which these activities need to be developed to have an advanced system. Clickers facilitate the process of teaching, and teacher assessment and report student learning outcomes.